THE EFFECT OF WORKLOAD AND MOTIVATION ON THE PERFORMANCE OF EMPLOYEES IN CORRECTIONAL INSTITUTION CLASS II A PEKANBARU - Wahyudal Wahyudal; Syamsul Bahri; Adi Setiawan; Supardi Supardi (STIE Bangkinang Publishing, 2022)
Employees as human resources who are the main component for an organization or agency, are required to provide the best performance results. Employees who have good performance can assist the agency in achieving the goals set by the agency. This study aims to determine the effect of workload and motivation simultaneously and partially on the performance of employees at Penitentiary Class IIA Pekanbaru. The population in this study was the warden at the Class II A Pekanbaru Correctional Institution (Lapas) in 2020, amounting to 56 people. The sampling technique used was the census technique, where the entire population was sampled, so the number of samples in this study was 56 samples. Data collection techniques using file research methods, questionnaires and interviews. Data analysis using multiple linear regression method. The result shows that based on partial analysis the independent variables (workload and motivation) have a significant effect on dependent variable (performance) of the Pekanbaru Class II A Correctional Institution employees. Based on simultant analysis (workload and motivation) have a significant effect on dependent variable (performance) of the Pekanbaru Class II A Correctional Institution employees. Based on the contribution of independent variables (workload and motivation) and the independent variable (performance) of the Pekanbaru Class II A Correctional Institution employees it is categorized as medium.